Avaliação do torque de fratura de mini-implantes submetidos à até três reutilizações - Miotti, Fabrício Lamberti (2016)
Orthodontists have been reusing mini-implants that fail after installation or that will be inserted in a new place due to mechanic needs in order to optimize clinical time. The aim of this study was to simulate the reuse of mini-implants up to three times and evaluate their potential weakness. We used 48 screws (Morelli, Sorocaba, Brazil), which were divided into four groups: C= Control, G1 = one reuse, G2 = two reuse, G3 = three reuse. In order to simulate inserts in patients mouths, we used pig iliac bone. After we insert screws on bone specimen, we removed, cleaned, and sterilized them by autoclaving. The guide at the machine we used allowed us to standardize installations. After all groups were submitted to their reuse periods, mini-implants were submitted to fracture, and the strongest force necessary to break them was measured by a digital axial torquemeter. We used bovine tibia specimens for fracture, because of its greater bone cortical and bone density. We used One Way ANOVA (Bonferroni post-hoc) to compare means of each group. Results showed differences statistically significant between G3 and the other groups. All mini-implants needed strength higher than recommended by the literature to be inserted into patients, even though we found differences in fracture resistance between groups.